JURIDICAL ANALYSIS OF THE SUPREME COURT REGULATION NUMBER 5 YEAR 2019 ARTICLE 8 CONCERNING APPLICATIONS AND CASE EXAMINATION IN MARRIAGE DISPENSATION REVIEWING FROM SIMPLE, QUICK AND LOW COST PRINCIPLES - Cut Auliani; Nelvitia Purba (Fox Justi : Jurnal Ilmu Hukum, 2022)
Marriage dispensation is the granting of a marriage permit by the court to a prospective husband or wife who is not yet old enough to marry. The age limit for marriage in Indonesia was originally regulated in Law No. 1 of 1974, namely if the man was 19 years old and the woman was 16 years old. The age limit for marriage in Indonesia is set so that it can regulate and guarantee the interests of the community in accordance with the culture of the community.The formulation of the problem in this paper are: 1) how is the application of the law, the factors constraining the abuse of underage marriage. 2) how to review the principle of fast, simple, and low cost of the Supreme Court Regulation No. 5 of 2019 Article 8 concerning the Application for Marriage DispensationThis legal research method is normative juridical, namely research to be carried out to obtain materials in the form of theories, concepts, legal principles and legal regulations related to the subject matter. men and women must have maturity both physically and mentally and physically if they want to get married so that when they get married they can build a good marriage without divorce. are not old enough, they must apply for a marriage dispensation and must be with the approval of the two prospective brides and also the parents of the bride and groom who are not old enough. This is in line with Law no.1 of 1974 and has been updated to become Law N0.16 of 2019.